Research in personnel and human resources management. Vol. 22 - Martocchio, Joseph J.; Ferris, Gerald R.; University of Illinois at Urbana-Champaign. (Bingley, U.K. : Emerald, 2003)
This series publishes monograph length conceptual papers designed to promote theory and research on important substantive and methodological topics in the field of human resources management. Volume 22 contains nine papers on critical issues in the field of human resources management, thus continuing the tradition of the series to develop a more informed understanding of the field.
Overview / Joseph J. Martocchio, Gerald R. Ferris -- The impact of team fluidity and its implications for human resource management research and practice / Brian R. Dineen, Raymond A. Noe -- Mentoring research : a review and dynamic process model / Connie R. Wanberg, Elizabeth T. Welsh, Sarah A. Hezlett -- The impact of telecommuting design on social systems, self-regulation, and role boundaries / David G. Allen, Robert W. Renn, Rodger W. Griffeth -- Research on employee creativity : a critical review and directions for future research / Jing Zhou, Christina E. Shalley -- The relationship between work-family human resource practices and firm profitability : a multi-theoretical perspective / Michelle M. Arthur, Alison Cook -- Toward understanding and managing stereotypical beliefs about older workers' ability and desire for learning and development / Todd J. Maurer, Kimberly A. Wrenn, Elizabeth M. Weiss -- Current directions and issues in personnel selection and classification / Walter C. Borman, Jerry W. Hedge, Kerri L. Ferstl, Jennifer D. Kaufman, William L. Farmer, Ronald M. Bearden -- Applying self-determination theory to organizational research / Kennon M. Sheldon, Daniel B. Turban, Kenneth G. Brown, Murray R. Barrick, Timothy A. Judge -- Beyond social exchange : new directions for organizational citizenship behavior theory and research / Kelly L. Zellars, Bennett J. Tepper.
Print version record
Keywords: Psychology -- Applied Psychology; Business & Economics -- Human Resources & Personnel Management; Personnel & human resources management; Personnel management